Diseminasi Pemanfaatan Tumbuhan Refugia sebagai Alternatif Pengendalian Hama Tumbuhan pada Lahan Pertanian Desa Sungai Dua - Yuwinti Nearti; Elmeizy Arafah; Acip Rakhmat; Muhammad Andri Zuliansyah (Penerbit Goodwood, 2022)
Purpose: PKM activities to encourage farmers to plant refugia around paddy fields to implement dissemination in the use of refugia plants in Sungai Dua Village. Efforts to increase the population of natural enemies are very important in maintaining the sustainability of the rice field ecosystem where the planting of refugia around is carried out in rice fields. Methodology/approach: Implementation activities through the introduction of innovations received through the process of listening, seeing, trying, evaluating, accepting, believing and implementing. Results/findings: There are many kinds of ornamental plants which are direct food sources for natural enemies (nectar and pollen) or can indirectly bring prey and hosts, in addition to controlling the microclimate based on the needs of natural enemies. Utilizing nectar and pollen from plants for natural enemies, both parasitoids and predators, can increase reproduction faster where more eggs will be produced. Conclusion: Community service activities carried out can be concluded as follows: Increasing the knowledge of PKM participants from members of the Sungai Dua Village Gapoktan experienced an increase in knowledge about the use of refugia plant technology as an alternative to environmentally friendly-based rice pest control